Nano-satellite Attitude Control System - Muhyi, Yaakop; Sazali, Yaacob, Prof. Dr.; Abdul Rahman, Mohd Saad; Zaridah, Mat Zain; Paulraj, Murugesa Pandiyan, Assoc. Prof. Dr.; Muthusamy, Hariharan; Ramachandran, Nagarajan, Prof. Dr.; Soh, Warren Kay; Ahmad Sabirin, Arshad (Universiti Malaysia Perlis (UniMAP), 2010)
A satellite maneuvers through orbit with the use of an attitude control system (ACS) to stay on course and always pointing towards earth reference. This maximizes the solar cell-sun and camera-earth coverage, a process made possible with hardware and software embedded in the satellite that continuously control and adjust for optimun performance.